The effectiveness of snakes and ladders as a learning media to increase students learning interest in Pancasila education at madrasah ibtidaiyah - Hasan, Muhammad; Faruq, Dukan Jauhari (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2025)
Despite the critical role of instructional media in education, its implementation remains suboptimal in many learning environments. This study develops and evaluates a diversity-themed snakes and ladders game as an innovative medium for enhancing student engagement in Pancasila Education among fifth-grade learners at MI Nahrul Muhith. Using the Research and Development (R&D) methodology with the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation), the study involved 16 participants. Data were collected through questionnaires and competency tests. Validation results demonstrated excellent suitability, with media experts rating the product at 88% and content experts at 84%, both meeting